Bendito: a narrativa em fluxos transmídia - Reis Neto, Ruy Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper discusses the evolution of Aristotelian narrative towards transmedia narratives. The first part of this process involved the study of classical narrative theories, especially the works of Aristotle (1999), Tzvetan Todorov (2003) and Robert Mckee (2006); the approach to cultural changes that have influenced the narrative, such as exposed by Gilles Deleuze and Felix Guatarri (1987) and their concept of rhizome, Michel Foucault (2008) with regard to his proposed interpretation of history, and Jean-François Lyotard (1984) on the meta-narratives; and the discussion of transmedia narratives as presented by Rosangella Leote (2007), Henrique Jenkins (2008), Vicente Gosciola (2012) and Lev Manovich (1999). This study supports and is elicited by the second part of this process, which involved planning for multimedia production whose format is shown here aiming at the future developmentof the work Bendito with the necessary sponsorship. The work is based on the classic narrative contained in the book of Job, adapting it through transmedia storytelling techniques to a conteporary production. The final production, once spored, should involve digital media, physical media and the public space. Attached to this volume is a CD with a short film Sacrificio (2010) mp4, a song Bendito seja o nome (2014).wav, and a folder with nine stereographic images. The short film was made by us previously, and serves as an example to a topic discussed on page 77. The music and the images were made by us during the course of this work, and are an integral part of it

Esta dissertação aborda a evolução da narrativa aristotélica para a narrativa transmídia. A primeira parte deste processo envolveu o estudo de teorias narrativas clássicas, principalmente as obras de Aristóteles (1999), Tzvetan Todorov (2003) e Robert Mckee (2006); a abordagem de algumas transformações culturais que teriam influenciado a narrativa, tais como expostas por Gilles Deleuze e Felix Guatarri (1987) e seu conceito de rizoma, Michel Foucault (2008) no que diz respeito à sua proposta de interpretação da história, e Jean-François Lyotard (1984) sobre as metanarrativas; e a discussão sobre narrativas transmídia tal como apresentadas por Rosangella Leote (2007), Henry Jenkins (2008), Vicente Gosciola (2012) e Lev Manovich (1999). Este estudo sustenta e é suscitado pela segunda parte deste processo, que envolveu o planejamento para uma produção multimídia, cuja formatação se mostra aqui visando o desenvolvimento futuro da obra Bendito, com o patrocínio necessário. A obra toma por base a narrativa clássica contida no livro de Jó, adaptando-a, através de técnicas narrativas transmídia, para uma produção contemporânea. A produção final, uma vez patrocinada, deverá envolver os meios digitais, suportes físicos e o espaço público. Anexado a este volume está um CD, com um curta metragem Sacrifício (2010) mp4, uma música Bendito seja o nome (2014).wav, e uma pasta com nove imagens estereográficas. O curta metragem foi realizado por nós em época anterior a este trabalho, e serve de exemplo a um tópico discutido à página 77. Já a música e as imagens foram realizadas por nós no decorrer deste trabalho, e são parte integrante deste
Keywords: Análise do discurso narrativo; Mitologia; Multimídia (Arte); Discourse analysis, Narrative